2019
DOI: 10.1155/2019/4612370
|View full text |Cite
|
Sign up to set email alerts
|

Can the Second to Fourth Digit Ratio (2D : 4D) Be a Marker to Determine Ankylosing Spondylitis Disease Activity?

Abstract: Objective. The length ratio of the index finger (2D) to the ring finger (4D) (2D : 4D ratio) is considered a biomarker of prenatal sex hormone exposure. The 2D : 4D ratio is influenced by prenatal androgen and estrogen levels. Because ankylosing spondylitis (AS) influences men more frequently and severely than women, androgens are proposed to be related to AS pathogenesis. Estrogens have immune-modulating effects and reduce AS disease activity. The aim of this study was to assess the relationship between 2D : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Nearly all the studies (n = 38, 92.7%) were published in or after 2010, with 26 of them (63.4%) in or after 2015. According to the study design, 31 studies (75.6%) were cross-sectional, 14,24,[27][28][29][31][32][33][34][35][36][37][38]40,41,[44][45][46][47][48][49][53][54][55][56][57][58][59][60][61][62] 9 studies (22.0%) were cohort studies, 15,25,30,39,42,43,[50][51][52] and 1 was a case-control study. 26 Twenty-five studies (61.0%) included patients with AS, 15,25,26,[30][31][32][33][36][37]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly all the studies (n = 38, 92.7%) were published in or after 2010, with 26 of them (63.4%) in or after 2015. According to the study design, 31 studies (75.6%) were cross-sectional, 14,24,[27][28][29][31][32][33][34][35][36][37][38]40,41,[44][45][46][47][48][49][53][54][55][56][57][58][59][60][61][62] 9 studies (22.0%) were cohort studies, 15,25,30,39,42,43,[50][51][52] and 1 was a case-control study. 26 Twenty-five studies (61.0%) included patients with AS, 15,25,26,[30][31][32][33][36][37]…”
Section: Resultsmentioning
confidence: 99%
“…All participants fulfilled SpA classification criteria, excluding 2 studies 32,40 that used general disease classification plus rheumatologic assessment, and 2 studies that did not identify their criteria. 28,44 Regarding the patients source, 21 studies (51.2%) included primary data or records from rheumatology departments, [24][25][26][27]29,31,33,35,36,38,39,41,45,47,49,50,54,55,58,59,60 8 studies (26.7%) included rheumatology patients from prospective cohorts, 14,15,42,43,51,52,56,62 6 studies included rheumatology patients from registries, 30,32,34,40,48,53 4 studies included patients from associations, 28,37,44,57 1 study included patients from the Bulgarian population, 46 and 1 cross-sectional study pooled 4 randomized controlled trials (RCTs). 61 The studies involved participants from 36 different countries, and most studies (80.5%) inc...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have suggested a link between the 2D:4D ratio and various diseases, including acne vulgaris 20,21 , seborrheic dermatitis 22 , psoriasis 23 , androgenetic alopecia 24 , thyroid disease 25 , lupus erythematosus 26 , multiple sclerosis 27 , ankylosing spondylitis 28 , some psychiatric disorders 29 , and some cancers (such as prostate and bladder) 30,31 . However, to our knowledge, there is not and published research on vitiligo and digit ratio.…”
mentioning
confidence: 99%